Effect of Type and Concentration of Different Water Soluble Polymer Solutions on Rheological Properties - Mohammed, Muhanned A.R.; Mohammed, Areej Jasim (Nahrain University College of Engineering Journal, 2009)
This research deals with experimental study of the effect of concentration of polymer solutions on rheological properties. All polymers studied in this work are water soluble, which are: XC-polymer, Carboxymethyl cellulose (two types), Hydroxyethyl cellulose and Polyvinyl alcohol. The rheological properties of these polymer solutions was investigated using a Couette coaxial cylinder rotational viscometer ( Fann model 35A ), by measuring shear stresses versus shear rates (i.e. the flow curve). 55 experiments were performed with different polymer solutions concentrations at temperature 30 C ( 1 C). It was found thatas polymer concentration increased, the flow behavior index (n) decreased and the consistency index (k) increased. This behavior reflects the fact that as polymer concentration increases the solution become far from Newtonian fluid. Correlations were found which describe the effect of polymerconcentration on n and k (for each polymer used in this study) and presented in a linear and exponential form respectively.